2017
DOI: 10.1097/sap.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Breast Augmentation Combining Fat Injection and Breast Implants in Patients With Atrophied Breasts

Abstract: Breast augmentation is a challenging issue in atrophied breasts related to breastfeeding. Here, we describe a modification combining breast implants and fat grafting to obtain a successful outcome without implant edge visibility and palpability.Thirty-four women with atrophied breasts underwent breast augmentation over a 6-year period. The breast implants were placed in the subglandular plane to obtain optimal filling and expansion of atrophied breast tissue. Autologous fat grafting was performed above the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…HBA is suitable for the following groups: (1) patients with insufficient soft tissue to cover the contour of the implant; (2) patients who want obvious cleavage and mellowing of the upper poles of the breasts; (3) patients with constricted lower pole breasts; (4) patients who are very concerned about the softness of the breast and want to reduce the proportion of implant volume while obtaining sufficient breast convexity; and (5) patients who can only accept round implants but require a natural appearance. Although there have been several reports on the surgical experience of HBA, 12–17 there is no reported comparative study on whether this operation brings higher satisfaction and additional risk. Therefore, this comparative study was designed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HBA is suitable for the following groups: (1) patients with insufficient soft tissue to cover the contour of the implant; (2) patients who want obvious cleavage and mellowing of the upper poles of the breasts; (3) patients with constricted lower pole breasts; (4) patients who are very concerned about the softness of the breast and want to reduce the proportion of implant volume while obtaining sufficient breast convexity; and (5) patients who can only accept round implants but require a natural appearance. Although there have been several reports on the surgical experience of HBA, 12–17 there is no reported comparative study on whether this operation brings higher satisfaction and additional risk. Therefore, this comparative study was designed.…”
Section: Discussionmentioning
confidence: 99%
“…Auclair and Anavekar 12 put forward the idea of using fat coverage to make circular endophytes into anatomical endophytes in 2015. Özalp and Aydinol 13 reported IBA with fat injection throughout the lower quadrants, which achieved 90% patient satisfaction. The observation of Maione et al 16 showed that the combination of high-profile round implants and fat grafting in BA could improve the aesthetic outcome and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following implant-based breast augmentation, fat grafting can be a great addition to blend and camouflage the implant borders, thus helping to achieve a more natural transition from native tissue to the augmented breast, especially in subglandular breast augmentation and in patients with thin skin. [36][37][38][39] On the other hand, for patients desiring removal of their breast implants, fat grafting can help restore some of the volume lost (►Fig. 1).…”
Section: Applications Of Fat Grafting In Aesthetic Breast Surgerymentioning
confidence: 99%
“…[ 3 4 ] Breast surgery alleviates many conditions such as small size, asymmetry, hypoplasia, ptosis, and chest wall anomalies. [ 5 6 7 ] It is the most common cosmetic surgery in the United States and is growing popular around the world. [ 8 ] For a woman with both volume decrease and ptosis of the breasts, not only augmentation but also mastopexy is required.…”
Section: Introductionmentioning
confidence: 99%